A censura ao cinema marginal na ditadura civil-militar brasileira (1968-1974) - Magalhães, Mauro Sérgio (2023)
The dissertation intends to analyze the censorship issued by the Department of Censorship and Public Diversions (DCDP) to works related to the cinematographic current called “Marginal Cinema”, which operated in Brazil partially in cinema theater circuits during the period of the Brazilian civil-military dictatorship, between 1968 and 1974. DCDP, as a representative body of the institutional apparatus for coercion of works of art in the country, including cinematographic ones, played a fundamental role in the imposition of censorship in Brazil. By means of a methodological focus, explaining broader fields of censorship, with the analysis of a vast documentary corpus, covering 81 opinions listed in the textual and image analysis of 19 works, the research aims to identify the most frequent veto natures in opinions of numerous censors and their perspectives on marginal cinematographic works, examine the criteria established for the works to be released with cuts, classified for audiences over 16, 18 or 21 years old or completely banned, as well as verifying whether the selected works had similar or different textual, aesthetic and visual narratives so that the modus operandi of censorship was differentiated or equal to the works of “Marginal Cinema”. Finally, the analysis focuses on the DCDP censorship mechanisms operating on a cinematographic current that is still little debated as a whole – although marginal works and filmmakers have already been investigated in a pertinent way, this happened in a more particular way. Therefore, reflections and further studies are deemed relevant that contribute to a greater appreciation and exaltation of “Marginal Cinema” with its textual and image messages, a cinematographic current repressed and suffocated by the DCDP censorship in the Brazilian civil-military dictatorship, but which did (and is) part not only of Brazilian cinematographic culture, but throughout the world